2010
DOI: 10.1111/j.1752-1688.2009.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Allelopathy and Toxicity in Prymnesium parvum1

Abstract: Some microalgae are able to kill or inhibit nutrient-competing microalgae, a process called allelopathy. Inhibiting or killing competitors enable these species to monopolize limiting resources, such as nitrogen and phosphorus. Prymnesium parvum is known to produce such allelopathic compounds, substances that seem identical to the ichthyotoxins identified from this species. Biotic and abiotic environmental factors influence not only growth rates but also toxin ⁄ allelopathic compounds production by P. parvum ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 75 publications
1
41
1
Order By: Relevance
“…The organism produces and releases toxic substances even under nutrientreplete conditions, but toxicity is increased under abiotic or biotic stress conditions including limitation of inorganic nutrients, nitrogen [N] and especially phosphorus [P] (Freitag et al, 2011;Grané li and Salomon, 2010). Prymnesium parvum is not able to feed on motile prey (Skovgaard and Hansen, 2003); it is supposed therefore that the role of the induced allelopathic/toxic compounds is to immobilize and lyse competing and prey algal species (Tillmann, 1998) and potential grazers (Tillmann, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The organism produces and releases toxic substances even under nutrientreplete conditions, but toxicity is increased under abiotic or biotic stress conditions including limitation of inorganic nutrients, nitrogen [N] and especially phosphorus [P] (Freitag et al, 2011;Grané li and Salomon, 2010). Prymnesium parvum is not able to feed on motile prey (Skovgaard and Hansen, 2003); it is supposed therefore that the role of the induced allelopathic/toxic compounds is to immobilize and lyse competing and prey algal species (Tillmann, 1998) and potential grazers (Tillmann, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that high pH increases the toxic activity of P. parvum (Shilo & Aschner 1953, while others have found the opposite (Padilla 1970, Igarashi et al 1998. Aeration can also increase the toxicity of P. parvum (Igarashi et al 1995), prompting suggestions that strong wind-mixing might enhance the toxicity of blooms (Granéli & Salomon 2010).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Factors associated with the toxicity of Prymnesium parvum were recently reviewed by Granéli & Salomon (2010). They proposed that the abundance and stage of population growth were important, with older and denser populations being more toxic than young, sparse populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations